New Paradigm of Indonesian Islamic Education: Analysis of Changes in the Relations of Islamic Education Institutions with Post-Reform Political Power - Cecep Sumarna (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Islamic Education Institutions (LPI) were born with different characters and ideologies from Dutch and Japanese educational institutions. This difference is still maintained even though Indonesia has declared itself independent. Only later in the reform era did the dynamics of the relationship between LPI and government power change. This study then examines changes in the relationship between the LPI and political power after the Reformation. This research will be carried out using qualitative methods and a historiographical approach. Researchers will use data on Indonesia’s social, political, and religious situation from when the Dutch colonized Indonesia until the temporary Indonesian period. This research then found a new change in the political movement of Islamic education in Indonesia in 1998. In this change, various Islamic educational institutions began to enter the political context and fill multiple positions in the government. Islamic educational institutions started to transform and become part of political power, which marked a paradigmatic change in the politics of Islamic education.